OPINION MINING METHODS IN ASSESSING SERVICE QUALITY: CASE STUDY OF SAUNG ANGKLUNG UDJO - El Fargha, Muhammad Avenzoor Al Hawarizmi; Iskandar, Budi Permadi (Journal of Business and Management, 2018)
Abstract. There has been continued research on the definition, modeling, measurement, data collection procedure and data analysis of service quality that lead to the development of base concept for the researchers. However, there are not many researches using opinion mining in qualitative approach from user-generated content website as the main data to measure service quality despite the increasing trend of companies start using internet/websites as marketing tools. This research aims to expand the horizon of knowledge within opinion mining by using qualitative sentiment analysis as the method to assess Saung Angklung Udjo’s quality service. This research used TripAdvisor’s Saung Angklung Udjo review in English and Indonesian as the data with using three polarities (positive, neutral and negative) while the aspects within the sentiment are based on 7Ps. In conclusion, opinion mining method using qualitative sentiment analysis proved to be applicable in assessing service quality of Saung Angklung Udjo. While in term of service quality, Saung Angklung Udjo only performed 6Ps out of 7Ps. Keyword: Service Quality, User-Generated Content, Opinion Mining, Qualitative Sentiment Analysis, 7P, Saung Angklung Udjo, Cultural Tourism, TripAdvisor.